2017
DOI: 10.1111/joss.12277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of swallowing and spitting on flavor intensity

Abstract: Does spitting provide the same flavor experience as swallowing? The objective of this research was to compare swallowing and spitting as procedures for evaluating flavor intensity. Participants evaluated taste or flavor intensity by both swallowing and expectorating water solutions, puddings, and cookies with added tastes and odors; each taste/odor was evaluated at several different concentrations. Flavor intensity was perceived to be more intense for caffeine solutions, ethyl butyrate solutions, and almond ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This may be explained partly by the wide variety in sweet-taste preferences 14 , 31 and bitter perception 31 across individuals. Large increase in oxyHb level after swallowing of bitter solution and disliked items may be derived by increased taste intensity due to stimulation of the posterior part of the tongue 32 , 33 . Furthermore, the aPFC is not the area responsible for direct processing of taste information, but is related to higher-order functions such as cognition, memory, thinking, execution etc.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained partly by the wide variety in sweet-taste preferences 14 , 31 and bitter perception 31 across individuals. Large increase in oxyHb level after swallowing of bitter solution and disliked items may be derived by increased taste intensity due to stimulation of the posterior part of the tongue 32 , 33 . Furthermore, the aPFC is not the area responsible for direct processing of taste information, but is related to higher-order functions such as cognition, memory, thinking, execution etc.…”
Section: Discussionmentioning
confidence: 99%
“…Lim's group [40] found a similar effect for citral and sucrose solutions, and later [41] for citral and coffee solutions. Although these studies demonstrated that an analytical strategy did not prevent taste-aroma interactions, their use of a sip and spit procedure is not representative of normal eating behavior, which has been shown to influence the sensory profile of samples, depending on the taste and flavor characteristics [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…However, the bitter-tasting SOA elicited one-shot images both before and after remarks evenly, despite being the most aversive stimulus. This may be explained by the fact that bitter stimuli stimulate taste cells in the foliate and circumvallate papillae situated at the back of the tongue better than those in the anterior tongue [ 37 , 38 ]. About half of the participants felt a stronger bitter taste after remarks at the timing for the bitter substance to reach the posterior tongue.…”
Section: Discussionmentioning
confidence: 99%